Multiaxial fatigue property of type 316 stainless steel using hollow cylinder specimen under combined pull loading and inner pressure - Takahiro Morishita; Yuta Takada; Takamoto Itoh (Fracture and Structural Integrity)
Stress controlled multiaxial fatigue test was carried out using a hollow cylinder specimen of type 316 stainless steel. A newly developed fatigue testing machine which can apply push-pull loading and reversed torsion loading and inner pressure to the hollow cylinder specimen was employed. 5 types of cyclic loading paths were employed by combining zero to pull axial and hoop stresses: a Pull (only axial stress), an Inner-pressure (only hoop stress), an Equi-biaxial (equi-biaxial stress by axial and hoop stresses), a Square-shape (trapezoidal waveforms of axial and hoop stresses with 90-degree phase difference) and a L-shape (alternately axial stress and hoop stress) loading paths. Since directions of principal stresses are fixed in all the tests, all of the loading paths are classified into ‘proportional loading’. In the Pull, the Inner-pressure and the Equi-biaxial tests, fatigue lives can be correlated on a unique line by a maximum equivalent stress based on von Mises. On the other hand, fatigue lives in the Square-shape and the L-shape tests were reduced comparing with that in the other tests, which was caused by yielding of larger plastic deformation.